2021
DOI: 10.3389/fphys.2021.629682
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Mediated Silencing of Pgants Shows Core 1 O-Glycans Are Required for Pupation in Tribolium castaneum

Abstract: Protein glycosylation is one of the most common and most important post-translational modifications. Despite the growing knowledge on N-glycosylation, the research on O-glycosylation is lagging behind. This study investigates the importance of O-glycosylation in the post-embryonic development of insects using the red flour beetle, Tribolium castaneum, as a model. We identified 28 O-glycosylation-related genes (OGRGs) in the genome of the red flour beetle. 14 OGRGs were selected for functional analysis based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
(103 reference statements)
1
3
0
Order By: Relevance
“…Throughout the development of T. castaneum, GalNAc and the core 1 O-glycans are present at relatively high levels, suggesting that these O-glycans play important roles in development and are probably required in each stage. This is in agreement with the lethal phenotype reported after disruption of the UDP-GalNAc: polypeptide N-acetylgalactosaminyltransferase (PGANT) activity, an enzyme required for the attachment of GalNAc to the peptide (Li et al, 2021;Tian & Ten Hagen, 2007;Tran et al, 2012;Yamamoto-Hino et al, 2015). The relative abundance of the O-GalNAcGal, O-GalNAcGal 2, and O-GalNAcGalGlcA glycans is significantly lower at the pupa stage compared with the larval stage.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Throughout the development of T. castaneum, GalNAc and the core 1 O-glycans are present at relatively high levels, suggesting that these O-glycans play important roles in development and are probably required in each stage. This is in agreement with the lethal phenotype reported after disruption of the UDP-GalNAc: polypeptide N-acetylgalactosaminyltransferase (PGANT) activity, an enzyme required for the attachment of GalNAc to the peptide (Li et al, 2021;Tian & Ten Hagen, 2007;Tran et al, 2012;Yamamoto-Hino et al, 2015). The relative abundance of the O-GalNAcGal, O-GalNAcGal 2, and O-GalNAcGalGlcA glycans is significantly lower at the pupa stage compared with the larval stage.…”
supporting
confidence: 89%
“…This could be attributed to the higher abundance of more complex mucin-type O-glycans, such as O-GalNAc(GalNAc)GlcA, O-GalNAcGalGlcAGlcNAc, and O-GalNAc(GlcNAcGlcA)GalGlcA, at this stage requiring the smaller mucin O-glycan structures for their synthesis. While the enzymes required for the synthesis of the more complex mucin-type O-glycans have not yet been identified (Li et al, 2020), PGANT activity was shown to be involved in the metamorphosis of T. castaneum (Dönitz et al, 2015;Li et al, 2021). For instance, downregulation of C1GalTA, the galactosyltransferase required for the elongation of O-GalNAc with a Gal residue, was shown to cause pupal lethality (Li et al, 2021;Lin et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both O-and N-glycosylation are important for insect physiology and development, as shown by RNAi experiments. Indeed, silencing of different enzymes important for the glycosylation process in insects caused failure of postembryonic development and wing formation [109,113].…”
Section: Role Of Lectins In Plantsmentioning
confidence: 99%